2019
DOI: 10.1007/s10826-019-01575-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-Consumer Marketing for Parent-Child Interaction Therapy: Impact of Language and Messenger

Abstract: Objectives: Parent-Child Interaction Therapy (PCIT) is an effective therapy to treat early onset disruptive behavior problems and child physical maltreatment. In order to support the successful implementation and sustainment of PCIT, strategies are needed to recruit parents into care, especially for racial and ethnic minority families, who often have lower rates of access and utilization of mental health services.Methods: This study investigated the impact of direct-to-consumer advertisements on parents' attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
(89 reference statements)
3
14
1
Order By: Relevance
“…However, completion rates were lower for fathers, parents of racial minority children, and single parents. This is consistent with other literature showing that these socio-demographic groups face unique barriers (Panter-Brick et al, 2014 ; Speth et al, 2015 ; Whisenhunt et al, 2019 ) and may benefit from tailored engagement strategies (Tully et al, 2017 ; Barnett et al, 2020 ). For example, it is particularly important for fathers to have clear information about what the program involves and to establish confidence in the abilities of the facilitator (Tully et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, completion rates were lower for fathers, parents of racial minority children, and single parents. This is consistent with other literature showing that these socio-demographic groups face unique barriers (Panter-Brick et al, 2014 ; Speth et al, 2015 ; Whisenhunt et al, 2019 ) and may benefit from tailored engagement strategies (Tully et al, 2017 ; Barnett et al, 2020 ). For example, it is particularly important for fathers to have clear information about what the program involves and to establish confidence in the abilities of the facilitator (Tully et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…For example, it is particularly important for fathers to have clear information about what the program involves and to establish confidence in the abilities of the facilitator (Tully et al, 2017 ). For racial and ethnic minorities, cultural appropriateness can be a key factor in influencing engagement (Barnett et al, 2020 ; Speth et al, 2015 ), and within ethnic minorities, different levels of acculturation may associate with different preferences (Perrino et al, 2018 ). Single parents may benefit from highly streamlined supports as they often experience additional financial and emotional burdens relative to dual parent households (Meier et al, 2016 ; Whisenhunt et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although therapists in the study suggested that testimonials from parents might improve engagement, it is important to test the effectiveness of these strategies, especially for diverse groups. For example, one study on direct-to-consumer marketing actually found that Spanish-speaking parents had higher intentions in pursuing PCIT if the testimonial was delivered by a therapist as opposed to a parent (Barnett et al, 2020). Therefore, it is important to tailor recruitment strategies for different populations, with a focus on increasing equity in who is accessing care.…”
Section: Discussionmentioning
confidence: 99%
“…To refine patient-directed communication, researchers have increasingly employed direct-to-consumer (DTC) marketing strategies to tailor messages about EBT for youth (Barnett et al, 2019; Gallo et al, 2015). Extensive data have shown that DTC marketing increases demand for prescription drugs (Schwartz & Woloshin, 2019), although its use by for-profit companies has not been without controversy (see Ventola, 2011).…”
mentioning
confidence: 99%